2011
DOI: 10.3357/asem.2856.2011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Basic Life Support Method in Simulated Microgravity

Abstract: The ER method can provide adequate depth and rate of ECC in simulated microgravity for 3 min to allow time to deploy a medical restraint system. There is, however, a physiological cost associated with it and a need to use the flexion of the arms to compensate for the lack of weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 16 publications
4
23
0
1
Order By: Relevance
“…Initial parabolic flight and ground-based simulation data showed the ER method as delivering an adequate rate and depth of chest compressions, although this was according to the 2005 resuscitation guidelines [5,42]. More recent data from ground-based simulations, using the updated 2010 guidelines, demonstrated that rescuers using the ER method fell slightly below par in terms of depth of compression but were able to maintain an adequate rate [45,47].…”
Section: Evetts-russomano Cpr Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Initial parabolic flight and ground-based simulation data showed the ER method as delivering an adequate rate and depth of chest compressions, although this was according to the 2005 resuscitation guidelines [5,42]. More recent data from ground-based simulations, using the updated 2010 guidelines, demonstrated that rescuers using the ER method fell slightly below par in terms of depth of compression but were able to maintain an adequate rate [45,47].…”
Section: Evetts-russomano Cpr Methodsmentioning
confidence: 99%
“…A safety carabineer was also attached to the volunteer's back. Figure 3(A) and (B) illustrates how CPR methods can be studied during microgravity simulations on Earth [5]. Another way to simulate microgravity for the performance of CPR is placing the mannequin in the vertical position supported by a wall, which avoids the use of the rescuer body weight during the external chest compressions, as represented in Figure 4.…”
Section: Body Suspension Device Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation is challenging because flight opportunities are limited, repetitive short windows of microgravity can make it difficult to assess methodologies or processes that normally require uninterrupted periods longer than 20-40 sec, and demonstrations may require additional equipment not easily utilized in-flight [12][13][14][15] . Furthermore, previous demonstrations of in vitro diagnostic (IVD) technologies used in, or designed for, reduced gravity are limited and much work remains unpublished.…”
Section: Introductionmentioning
confidence: 99%